HUBUNGAN KECERDASAN KINESTETIK DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PJOK PESERTA DIDIK KELAS XI UPT SMA NEGERI 6 SINJAI - Andi Anwar Ishar; Hasnah Hasnah; Andi Nahdia T Walinga; M. Adam Mappaompo (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This study aims to see whether there is a positive relationship between kinesthetic intelligence and PJOK learning outcomes; to see whether there is a positive relationship between learning motivation and PJOK learning outcomes; and whether both (kinesthetic intelligence and learning motivation) jointly have a positive relationship with PJOK learning outcomes of UPT SMAN6 Sinjai students. This research is an ex post facto research that is correlational. Data collection was carried out on the research sample, namely students in class XI UPT SMAN6 Sinjai using a non-test instrument in the form of a questionnaire in the form of a Likert scale to determine the level of kinesthetic intelligence and students' learning motivation. Where the instrument used is an instrument that has a known level of validity and reliability. Meanwhile, for students' PJOK learning outcomes, the researchers looked directly at the reports of learning outcomes for one semester. The results of the research and analysis show that the kinesthetic intelligence of students in class XI UPT SMAN6 Sinjai is in the high category, the learning motivation of students in class XI UPT SMAN 6 Sinjai is in the high category, the PJOK learning outcomes of students in class XI UPT SMAN6 Sinjai are in the high category. in the very high category, there is a positive relationship between Kinesthetic Intelligence and PJOK Learning Outcomes of Class XI Students of UPT SMAN6 Sinjai. There is a positive relationship between Learning Motivation and PJOK Learning Outcomes of Class XI Students of UPT SMAN6 Sinjai. , There is a positive relationship between Kinesthetic Intelligence and Learning Motivation together with PJOK Learning Outcomes of Class XI Students of UPT SMAN6 Sinjai.